2021
DOI: 10.1002/bies.202100114
|View full text |Cite
|
Sign up to set email alerts
|

The gamma‐tubulin ring complex: Deciphering the molecular organization and assembly mechanism of a major vertebrate microtubule nucleator

Abstract: Microtubules are protein cylinders with functions in cell motility, signal sensing, cell organization, intracellular transport, and chromosome segregation. One of the key properties of microtubules is their dynamic architecture, allowing them to grow and shrink in length by adding or removing copies of their basic subunit, the heterodimer αβ-tubulin. In higher eukaryotes, de novo assembly of microtubules from αβ-tubulin is initiated by a 2 MDa multi-subunit complex, the gamma-tubulin ring complex (γ-TuRC). For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
(177 reference statements)
1
8
0
Order By: Relevance
“…Therefore, our results suggest that the formation of heterogeneous microtubule lattices is an intrinsic property of tubulin polymerization, which is firmly regulated in cells. One key regulatory factor could be the γ-tubulin ring complex (γTuRC), which imposes the 13 protofilament organization to a nascent microtubule (Böhler et al, 2021). But how this structure is preserved during microtubule elongation remains unclear, especially if one considers a two-dimensional assembly process where the lattice can vary in terms of protofilament number, helix-start number, or lattice type during elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that the formation of heterogeneous microtubule lattices is an intrinsic property of tubulin polymerization, which is firmly regulated in cells. One key regulatory factor could be the γ-tubulin ring complex (γTuRC), which imposes the 13 protofilament organization to a nascent microtubule (Böhler et al, 2021). But how this structure is preserved during microtubule elongation remains unclear, especially if one considers a two-dimensional assembly process where the lattice can vary in terms of protofilament number, helix-start number, or lattice type during elongation.…”
Section: Discussionmentioning
confidence: 99%
“…These dynamic structures are constantly elongated or shortened in all phases of cell cycle by adding or removing tubulin heterodimers from the ends of microtubules [ 199 , 200 , 201 , 202 ]. The assembly of protofilaments to microtubules is done spontaneously, with a number of protofilaments between 9 and 16, resulting in microtubules with different diameters [ 203 ]. It is known that the organization of microtubules changes significantly during the cell cycle.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Recent cryo-electron microscopy (cryo-EM) structures of human and Xenopus gTuRC revealed that two adjacent GCP2/3 pairs are replaced by a GCP4/5 pair and a GCP4/6 pair, and that a "luminal bridge" is positioned inside the cone (27)(28)(29)(30). This bridge contains an actin-like molecule and two copies of mitoticspindle organizing protein 1 (MZT1) and the N-terminal extensions (NTEs) of one GCP3 and GCP6, forming MZT1/3NTE and MZT1/6NTE modules (31), which have been proposed to be important for complex assembly and stability (32)(33)(34). The function of the actin-like molecule in the gTuRC is less understood, much like the unclear role of an "end protrusion" that extends from the last GCP3 on the outside of the complex, possibly representing another MZT1-like/ NTE module (28)(29)(30)(31)35).…”
mentioning
confidence: 99%